2022
DOI: 10.3390/d14100848
|View full text |Cite
|
Sign up to set email alerts
|

New Molecular-Based Phylogeny of Mussel-Associated Mites Reveals a New Subgenus and Three New Species Representing an Example of a Host-Driven Radiation in Indochina and Confirms the Concept of Division of the Genus Unionicola Haldeman, 1842 (Acari: Unionicolidae) into Numerous Subgenera

Abstract: Here we describe a new subgenus and three new species of parasitic water mites in the genus Unionicola (Acari: Hydrachnidia) from Myanmar: Myanmaratax subgen. nov., Unionicola (Myanmaratax) savadiensis subgen. and sp. nov. (hosts: Lamellidens savadiensis and L. generosus), U. (My.) generosa sp. nov. (the same hosts), and U. (My.) trapezidens sp. nov. (hosts: Trapezidens dolichorhynchus and T. angustior). These taxa were identified based on a two-gene phylogenetic analysis (COI + 28S), which also confirms the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…(M.) savadiensis (n=8), U. generosa (n=4), U. trapezidens (n=4), U. robacki (n=9), U. sella (n=2) and U. ypsilophora (n=1). COI sequence data were additionally taken from Chapurina et al (2021Chapurina et al ( , 2022a and Pešić et al (2021), and downloaded from the respective sequence data archives. Sequences were aligned with MUSCLE (Edgar 2004).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…(M.) savadiensis (n=8), U. generosa (n=4), U. trapezidens (n=4), U. robacki (n=9), U. sella (n=2) and U. ypsilophora (n=1). COI sequence data were additionally taken from Chapurina et al (2021Chapurina et al ( , 2022a and Pešić et al (2021), and downloaded from the respective sequence data archives. Sequences were aligned with MUSCLE (Edgar 2004).…”
Section: Methodsmentioning
confidence: 99%
“…(Myanmaratax) brandti Vidrine, 1985 from the same host species. It is possible that the latter record was actually a mite belonging to one of the species described in the new subgenus in Chapurina et al (2022a), but lacking evidence supporting this, the record is considered doubtful. Chapurina et al (2022a, b) reported a number of species from Lamellidens Simpson, 1900 as gill mites from Myanmar, including U. diversipes, U.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the obtained molecular data, the authors reconstructed the phylogeography for the genus Niphargus. Chapurina et al [5] describe a new subgenus and three new species of the parasitic water mites in the genus Unionicola from Myanmar, Southeastern Asia. The data obtained by the authors confirm that Unionicola mites are narrow host specialists that are associated with either one or a few closely related freshwater mussel species belonging to one or two sister genera.…”
Section: Taxonomy Phylogeny and Evolutionmentioning
confidence: 99%